Muscle Ageing and Sarcopenia Study (MASS) Lifecourse: a valuable resource for understanding skeletal muscle ageing - Rachel Cooper; Christopher Hurst; Holly Syddall; Helen Atkinson; Jonathan G. Bunn; Daniela Carpinelli; Antoneta Granic; Susan J. Hillman; Emma Grace Lewis; Claire McDonald; Katie Sloan; Karen Suetterlin; et al. (GeroScience, 2026)

Assessing microplastics contamination in unviable loggerhead sea turtle eggs - Lindsay F. Curl; Samantha A. Hurst; Christopher M. Pomory; Margaret M. Lamont; Alexis M. Janosik (Science of The Total Environment, 2024)

Dysregulation of microRNAs may contribute to neurosensory impairment in Arctic cod (Boreogadus saida) following CO2 exposure - Cara C. Schweitzer; Carolina A. Bonin; Christopher Magel; Thomas P. Hurst; Andrij Z. Horodysky (Frontiers in Marine Science, 2023)
MicroRNAs (miRNAs) are epigenetic markers with a key role in post-transcriptional gene regulation. Several studies have described the dysregulation of miRNAs in temperature and hypoxic stress responses of marine organisms, but their role in the response to acidification conditions has remained relatively underexplored. We investigated the differential expression of miRNAs in whole brain tissue of Arctic cod ( Boregogadus saida) exposed to elevated aqueous CO 2 levels representative of future climate change predictions. We detected the expression of 17 miRNAs of interest that are either directly or indirectly associated with reduced auditory performance; 12 of the 17 miRNAs showed significant differential expression in high treatment vs. low (control) aqueous CO 2 conditions. Target gene predictions indicated that these miRNAs are likely involved with inner ear maintenance, hair cell degradation, age-related hearing loss, neural inflammation, and injury. The highest differential expression was observed in mir-135b, which is linked with increased neural inflammation and injury that may be associated with neurosensory dysfunction. Collectively, these results elucidate the contributions of miRNA mechanisms underlying CO 2 -induced sensory deficits in fishes facing abiotic environmental change and suggest strong potential for this approach to yield novel insights into the mechanistic effects of climate change on marine organisms.

The ecological significance of lipid/fatty acid synthesis in developing eggs and newly hatched larvae of Pacific cod (Gadus macrocephalus) - Benjamin J. Laurel; Louise A. Copeman; Thomas P. Hurst; Christopher C. Parrish (Marine Biology, 2010)

Characterization of Cauxin in the Urine of Domestic and Big Cats - Lynn McLean; Jane L. Hurst; Christopher J. Gaskell; John C. M. Lewis; Robert J. Beynon (Journal of Chemical Ecology, 2007)